Career Choice Tendency of State Senior High School Students in Industry 4.0 Era - Zahro, Zulfianti Rosyida; Setiyowati, Arbin Janu; Simon, Irene Maya (Jurnal Kajian Bimbingan dan Konseling, 2020)
This study aims to describe the career choice tendency of state senior high school students in the industry 4.0 era. This research is quantitative descriptive research, in the form of a percentage, involving 236 students as the participants. The sample was chosen using cluster random sampling technique. For the instrument, this research used a questionnaire of students’ career choice tendency in the industry 4.0 era. The obtained data were analyzed using percentage descriptive statistics. The findings reveal that 93% of senior high school students in Malang city tend to choose a career in the business and repair services sector, then followed by 89% of students who select the trading and government administration sector. This study can be fundamental and primary data for school counselors in providing guidance and counseling services in the career field, such as career information services. This service belongs to one of the students’ consideration to carefully plan their career to achieve a bright future.